Potentiated Electron Transference in alpha-Ag2WO4 Microcrystals with Ag Nanofilaments as Microbial Agent - Longo, Valeria M.; De Foggi, Camila C. [UNESP]; Ferrer, Mateus M.; Gouveia, Amanda F.; Andre, Rafaela S.; Avansi, Waldir; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Andres, Juan; Cavalcante, Laecio S.; Hernandes, Antonio C.; Longo, Elson [UNESP] (Amer Chemical Soc, 2014)
This study is a framework proposal for understanding the antimicrobacterial effect of both alpha-Ag2WO4 microcrystals (AWO) synthesized using a microwave hydrothermal (MH) method and alpha-Ag2WO4 microcrystals with Ag metallic nanofilarnents (AWO:Ag) obtained by irradiation employing an electron beam to combat against planktonic cells of methicillin-resistant Staphylococcus aureus (MRSA). These samples were characterized by X-ray diffraction (XRD), FT-Raman spectroscopy, ultraviolet visible (UV-vis) measurements, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and high resolution transmission electron microscopy (HRTEM). The results reveal that both AWO and AWO:Ag solutions have bacteriostatic and bactericidal effects, but the irradiated sample is more efficient; i.e., a 4-fold of the MRSA planktonic cells as compared to the nonirradiated sample was observed. In addition, first principles calculations were performed to obtain structural and electronic properties of AWO and metallic Ag, which provides strong quantitative support for an antimicrobacterial mechanism based on the enhancement of electron transfer processes between alpha-Ag2WO4 and Ag nanoparticles.